Curriculum System of Preschool Education under the Background of AR Intelligence - Zhufeng Ye; Jirarat Sitthiworachart (My University, 2021)
With the advent of the "Internet +" era, the rapid development of mobile handheld devices such as smartphones and iPads provides a suitable platform for the development of augmented reality technology. In the field of education, the study of enriching teaching scenarios and deepening students' understanding through AR technology has attracted the attention of many experts and scholars at home and abroad. Among them, AR technology has great room for development in the field of preschool education. The article analyzes the literature, compares its research content and methods, specifically explores the application examples of AR technology in the field of preschool education, summarizes the three main directions of AR in the development of early childhood education (children books, children educational games and classroom practice), and focuses on AR in The characteristics and advantages of early childhood education applications, so as to design learning tools suitable for children's learning.
Keywords: Augmented Reality Applications; Environmental Engineering and Cultural Studies; AI and Big Data Applications